Teaching and Researching the Pronunciation of English: Studies in Honour of Włodzimierz Sobkowiak - Waniek-Klimczak, Ewa (Springer, 2016)
The book contains contributions from practitioners and theoreticians who explore the pronunciation of English from various perspectives: phonetic, phonological, psycholinguistic and sociolinguistic. In accordance with the unifying theme of the volume, individual contributions investigate the characteristics of a foreign accent, its production and perception, study the development of methods and techniques in pronunciation teaching, evaluate their use in classroom materials and in the classroom itself, and investigate the conditions for second language learning and teaching from the perspective of learners and teachers. The book offers a unique combination of a scholarly research with practical applications, inspired over the years by the work of Professor Włodzimierz Sobkowiak, who has researched pronunciation teaching and pioneered technology-oriented, corpus-based approaches to the study of English pronunciation in Poland.